Nuskha-shinākht : Pizhūhishnāma-yi nuskhashināsi-yi nusakh-i khaṭṭi-yi Fārsī - Qalʿa, ʿAlī Ṣafarī Āq; Afshār, Īraj (Miras Maktoob, ISBN: 9789004365452., 2019)
This is a work on the codicology of Islamic manuscripts with a special emphasis on manuscripts in Persian. According to the great Iranian codicologist Iraj Afshar it is the most detailed and complete work in its field in Persian after Mahdī Bayānī's Kitābshināsi-yi kitāb-i khaṭṭī , published posthumously in 1353/1974-75. The work is divided into two parts: the first part discusses all the elements related to the physical existence of a manuscript in the order in which these come to be, while the second part describes various aspects of the embellishments with which manuscripts were often provided once the codex had been produced. The work is extremely detailed and comes with many photographs in illustration of the text. Special attention is drawn to the care with which the author records the terminology around Islamic manuscripts in Persian. As such, this work may be regarded as complementary to A. Gacek's Arabic Manuscripts and The Arabic Manuscript Tradition.